2004
DOI: 10.4049/jimmunol.173.12.7594
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD44 and Hyaluronan in Neutrophil Recruitment

Abstract: Lymphocyte CD44 interactions with hyaluronan localized on the endothelium have been demonstrated to mediate rolling and regulate lymphocyte entry into sites of chronic inflammation. Because neutrophils also express CD44, we investigated the role of CD44 and hyaluronan in the multistep process of neutrophil recruitment. CD44−/− and wild-type control mice were intrascrotally injected with the neutrophil-activating chemokine, MIP-2, and leukocyte kinetics in the cremasteric microcirculation were investigated 4 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
171
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 39 publications
10
171
1
Order By: Relevance
“…Several studies have shown a positive role of CD44 in inflammatory cell recruitment, 10,25,[36][37][38][39][40][41] whereas other investigations reported enhanced inflammatory cell migration in the absence of CD44. 8,9,24,35 This discrepancy is probably because of the differences in the cell type studied, the stimulus and organ involved, and the severity of the insult.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have shown a positive role of CD44 in inflammatory cell recruitment, 10,25,[36][37][38][39][40][41] whereas other investigations reported enhanced inflammatory cell migration in the absence of CD44. 8,9,24,35 This discrepancy is probably because of the differences in the cell type studied, the stimulus and organ involved, and the severity of the insult.…”
Section: Discussionmentioning
confidence: 93%
“…51 In addition, CD44 (which is constitutively expressed by immune cells) was shown to be involved in the recruitment of monocytes and neutrophils to the site of inflammation. 52,53 CD44-hyaluronic acid interaction could be induced by inflammatory stimuli such as cytokines. 54 CD44 protein was recently found to be increased on peripheral leukocytes from term pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in dermal ECs, TLR4 signal induced by HA fragments increases expression of the cell adhesion molecule ICAM-1 and the chemokine MIP-2, which are involved in the recruitment of neutrophils (42). CD44/HA interactions mediate neutrophil and lymphocyte adhesion and migration across endothelium (43). Additionally, siRNA inhibition of endogenous hyaluronidases in fibroblasts subjected to collagen-induced arthritis decreases TLR4 expression, NF-B activation, and IL-1␤ production elicited by TNF␣ stimulation (44).…”
Section: Discussionmentioning
confidence: 99%